2022
DOI: 10.4103/jfmpc.jfmpc_1773_21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of hemophilia B patients from Karnataka

Abstract: Background: The most prevalent severe inherited hemorrhagic condition is hemophilia, which means “love of blood.” Hemophilia A and B are caused by a lack or malfunction of the factor VIII and factor IX proteins. Objective: The present study is to determine the prevalence and clinical profile of hereditary coagulation disorder, particularly hemophilia B, in Karnataka. Methods: The study comprised 150 HB patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…A family history has been detected in 45-65% of HB cases. In our study, the family history has been observed in 55% of patients [19,[21][22]. This indicates the sporadic nature of disease due to spontaneous genetic mutations.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A family history has been detected in 45-65% of HB cases. In our study, the family history has been observed in 55% of patients [19,[21][22]. This indicates the sporadic nature of disease due to spontaneous genetic mutations.…”
Section: Discussionsupporting
confidence: 56%
“…Similar to other studies, the age at the time of diagnosis for patients with severe HB was signi cantly lower than that for patients with mild or moderate cases. A study by Kulkarni et al found that in severe patients, bleeding started at a mean age of 2.0 1.0 years, in moderate patients at 7.5 2.8 years, and in mild patients at 10 3.5 years [19]. However, in a study of 35 Pakistani patients, the median age at rst bleeding was not signi cantly different between severe (12.0 months), moderate (6.0 months), and mild (15.5 months) HB patients [20].…”
Section: Discussionmentioning
confidence: 99%